Imidazolopyrazine based thermally activated delayed fluorescence: Synthesis, property and the application for solution-processed OLEDs. (3rd December 2022) - Zhou, Jiachun; Wang, Shengyue; Chen, Xinrui; Fan, Jiang; Wang, Yafei
Abstract: Solution-processed thermally activated delayed fluorescence (TADF) emitter is a promising strategy in organic light-emitting device (OLED). In this contribution, the novel emitters named IPy-Ac was synthesized and characterized, in which imidazolopyrazine (IPy) moiety is used as the acceptor and acridine (Ac) is employed as the donor group. In addition, the corresponding emitters (Py-Ac) using pyrazine (Py) as the acceptor are prepared to comparison. Both compounds exhibit clear TADF character in the host matrix. The molecular structure-property relationship is investigated via both calculated and experimental methods. Using both emitters as the dopant, solution-processed OLEDs are fabricated and the IPy-Ac based device achieves the best performance with a maximum external quantum efficiency of 6.36%. This research demonstrates that the IPy moiety can be a promising electron acceptor for the design of TADF materials. Graphical abstract: Two novel TADF emitters bearing imidazolopyrazine/pyrazine as the acceptor moiety were designed and synthesized. The molecular structure-property relationship was explored in detail. The solution-processed OLEDs based on these two emitters achieved a maximum EQE of 6.36% at 504 nm. Image 1 Highlights: Two novel imidazolopyrazine/pyrazine-based emitters are prepared. Both emitters exhibit TADF character in host matrix. The molecular structure-property relationship is investigated. The solution-processed OLEDs achieve a maximum EQE of 6.36% at 504 nm.